An estimate of the economic burden of venous leg ulcers associated with deep venous disease. (February 2022) - Kolluri, Raghu; Lugli, Marzia; Villalba, Laurencia; Varcoe, Ramon; Maleti, Oscar; Gallardo, Fernando; Black, Stephen; Forgues, Fannie; Lichtenberg, Michael; Hinahara, Jordan; Ramakrishnan, Saranya; Beckman, Joshua A.
Introduction: Venous leg ulcers (VLU) embody the most severe stage of the broad spectrum of chronic venous disease. Approximately 40% of patients with VLU present with the underlying deep venous disease (DVD). Although the data are scarce, these deep venous disease-related VLU (DRV) are thought to have higher recurrence rates and a substantial economic burden. The objective of this study was to assess the economic burden of DRV across Australia, France, Germany, Italy, Spain, the UK, and the USA. Methods: A comprehensive literature review was undertaken to identify publications documenting the incidence and prevalence of VLU and DRV, medical resource utilization, and associated costs of DRV. Findings from this literature review were used to estimate the economic burden of illness, including direct medical costs over a 12-month interval following initial presentation of a newly formed DRV. Results: Total annual incidence of new or recurrent DRV in Australia, France, Germany, Italy, Spain, UK, and the US are estimated at 122, 000, 263, 000, 345, 000, 253, 000, 85, 000, 230, 000, and 643, 000 events, respectively, in 2019. Incidence ranges from 0.73 to 3.12 per 1000 persons per year. The estimated annual direct medical costs for patients managed conservatively in these geographies total ~ $10.73 billion (USD) or $5527 per person per year. Conclusion: The availability of published data on the costs of VLU care varies widely across countries considered in this analysis. Although country-specific VLU practice patterns vary, there is a uniform pattern of high-cost care.